Chest Pain and Prehospital Delay - Stevanović, Marija M; Živanović, Slavoljub (Medicinski časopis, 2021)
Aim was to show the time duration of chest pain in patients with Angina pectoris (AP) and myocardial infarction (MI) prior to reporting to the ambulance and  patients' self management of the pain.Materials and methods: The study  was done between 1st August 2014th and 1st October 2018th in the infirmary of EMS in Belgrade. The study involves 169 patients with confirmed or suspected diagnosis of an acute MI or AP.Results: Patients with AP waited most commonly between 1-2 hours, while the patients with MI waited between 2-6 hours from the pain onset until contacting EMS. Most number of patients with MI (17) as well as with AP (83) didn’t take any kind of therapy, while some patients administered one or more drugs in order to relieve the pain. In patients with AP drugs of choice were antihypertensive medications (31%) and in MI patients Nitroglycerin and analgesics. All patients previously diagnosed with MI and AP have self-administered Nitroglycerin in 22.6% of cases.Conclusion: Patients with AP wait less when having chest pain before calling EMS from patients with Acute Coronary Syndrome, but their self-administered drugs of choice were antihypertensive medications. Nitroglycerine as the first appropriate drug of choice is used less and in most cases patients don't even have it available.
Keywords: Key words: chest pain, primary healthcare, self-administered drugs, time delay